Gastrointestinal Ultrasonography of Normal Standardbred Neonates and Frequency of Asymptomatic Intussusceptions. (7th August 2014) - Abraham, M.; Reef, V.B.; Sweeney, R.W.; Navas de Solís, C.
<x xml:space="preserve">Abstract</x> Background Ultrasonographic appearance of the gastrointestinal (GI) tract of equine neonates has not been completely described. Objectives To describe (1) sonographic characteristics of the GI segments in normal nonsedated equine neonates, (2) intra‐ and interobserver variation in wall thickness, and (3) the sonographic appearance of asymptomatic intussusceptions, and (4) to compare age and sonographic findings of foals with and without asymptomatic intussusceptions. Animals Eighteen healthy Standardbred foals ≤5 days of age. Methods Prospective, cross‐sectional blinded study. Gastrointestinal sonograms were performed stall‐side. Intraobserver variability in wall thickness measurements was determined by calculating the coefficient of variation (CV). The Bland–Altman method was used to assess interobserver bias. Student's t‐test and Fisher's exact test were used to test the association among presence of intussusceptions, age, and selected sonographic findings. Results The reference ranges (95% predictive interval) for wall thickness were 1.6–3.6 mm for the stomach, 1.9–3.2 mm for the duodenum, 1.9–3.1 mm for the jejunum, 1.3–2.2 mm for the colon, and 0.8–2.7 mm for the cecum. Intraobserver wall thickness CV ranged from 8 to 21% for the 2 observers for 5 gastrointestinal segments. The interobserver bias for wall thickness measurements was not significant except for the stomach (0.14 mm, P < .05) and duodenum (0.29 mm, P < .05). Diagnostic images of mural blood flow could not be obtained. Asymptomatic intussusceptions were found in 10/18 neonates. Associations between sonographic variables or age and the presence of intussusceptions were not found. Conclusions and Clinical Importance Sonographic characteristics of the GI tract of normal Standardbred neonates can be useful in evaluating ill foals. Asymptomatic small intestinal intussusceptions occur in normal Standardbred neonates.